EFFECT OF POLYPHENOLIC COMPOUNDS ISOLATED FROM CARTHAMUS TINCTORIUS AND CALENDULA OFFICINALIS L., ON FUNCTIONAL ACTIVITY OF IMMUNE CELLS UNDER CONDITIONS OF CYTOSTATIC IMMUNOSUPPRESSION - N. V. Masnaya; N. V. Isaikina; Ye. Yu. Sherstoboev; G. I. Kalinkina (Бюллетень сибирской медицины)
The purpose of the study – to study the effect of polyphenolic compounds extracted from the flowers of safflower oil and calendula, the functional activity of immune cells in cytotoxic immune suppression.Conventional methods determined the total number of splenocytes, relative (%) and absolute (106), the number of antibody-forming cells (AFC) in the spleen of mice by local hemolysis by Cunningham.Evaluated the effect of compounds of natural origin on the cellular immune response in the delayed-type hypersensitivity (DTH). Phagocytic activity of peritoneal macrophages was determined by the method based on the intensity of their capture ink particles. We studied the functional activity of peritoneal macrophages by NBT test (spontaneous and stimulated). Studies were conducted on male mice Category 1 (conventional linear mouse) line CBA/CaLac aged 2–2.5 months, weighing 20–22 g. After the introduction mice line CBA/CaLac of polyphenolic compounds derived from flowers of Carthamus tinctorius and flowers of Calendula officinalis L. during the 5-day course in dose 50 mg/kg was observed stimulation of the humoral immune response (total number of splenocytes, the number of antibodies in the spleen cells) and the functional activity of macrophages and Immunomodulating effect on the humoral immunity and the functional activity of macrophages after a single injection of cyclophosphamide in dose 250 mg/kg. Immunotropic activity of polyphenolic compounds is higher than that those of the reference product of tincture of Echinacea purpurea.